Educational utility of an online video‐based teaching tool for sinus and skull base surgery. Issue 2 (24th March 2021) - Fan, Timothy; Workman, Alan D.; Koch, George; Rathi, Vinay K.; Scangas, George A.; Metson, Ralph
Abstract: Objective: Surgical education has undergone major changes in recent years, as hands‐on learning opportunities have been replaced or supplemented with online tools. The goal of this project is to examine the educational impact of a surgical training website, SinusVideos.com, on otolaryngologists at various levels of training. Methods: Visitors to the website were asked to complete a survey after viewing a narrated video of a surgical procedure. Surveys were analyzed for demographics, needs assessment, and educational impact. Results: A total of 105 completed surveys were completed by 68 (64.8%) attendings/practicing physicians, 32 residents/fellows (30.5%), and 5 medical students (4.8%). Whereas 14.3% of viewers reported online videos as their primary source for surgical preparation, 70.5% considered them important secondary supplements. After viewing a video, 92.4% of respondents reported a gained confidence in performing the surgery, and 62.9% said the video altered how they would perform the surgery in the future. Viewers' ratings of their knowledge (on a 1‐7 Likert scale) of a particular surgical procedure before vs after watching the observed procedure increased significantly for participants at all levels of training—medical students (2.8 before vs 5.4 after, P  < .01), residents/fellows (4.8 before vs 5.8 after, P  < .0001), and attendings/practicing physicians (5.6 before vs 6.4 after, P  < .0001). Conclusion: High quality online surgical videos appear to be an effective learning tool for surgical trainees and practicing physicians alike. The educational benefit of such tools, as well as their widespread accessibility, makes them a powerful instrument for the training of surgeons worldwide. Level of Evidence: Level 5. Abstract : Surgical education has undergone major changes in recent years, as hands‐on learning opportunities have been replaced or supplemented with online tools. The goal of this project is to examine the educational impact of a surgical training website, SinusVideos.com, on otolaryngologists at various levels of training. High quality online surgical videos appear to be an effective learning tool for surgical trainees and practicing physicians alike, and the educational benefit of such tools, as well as their widespread accessibility, make them a powerful instrument for the training of surgeons worldwide.